AKADEMIK LITSEY O‘QUVChILARINING FIZIKA FANIDAN TANQIDIY FIKRLAShINI RIVOJLANTIRIShDA DEBAT METODIDAN FOYDALANISh - Batirov, B.B. (SCIENCE and SOCIETY, 2025)
This article discusses the use of debates as a method to activate critical thinking in students of academic lyceums during physics lessons, with a focus on semiconductor materials. The advantages of debates for developing skills in argumentation, analysis, and decision-making are analyzed. Special attention is given to the topic of semiconductors, their role in modern technologies, and their potential for use in the educational process. Examples of debate topics and methodological recommendations for conducting them are provided. The evaluation of debate results includes both scientific accuracy and the development of communication and analytical skills in students.
Keywords: debates; critical thinking; semiconductor materials; physics; educational process; argumentation; analytical skills; educational technologies; academic lyceums